(untitled) (Coordinates of Public Administration, 2025)
The article provides a comprehensive analysis of the legal, institutional, and managerial foundations of social adaptation and reintegration of veterans of the Russian-Ukrainian war under martial law and post-war reconstruction of Ukraine. The dynamic nature of the social adaptation process, which encompasses medical, psychological, socio-domestic, professional, and socio-political dimensions, is revealed, and reintegration is defined as the final phase of restoring the subjectivity and social autonomy of a veteran. The evolution of the regulatory framework is analyzed, in particular, the current versions of the laws of Ukraine on the status of war veterans, social protection of military personnel, pensions, rehabilitation of persons with disabilities, national resistance, and perpetuation of memory, and internal conflicts, duplication, and fragmentation of regulation are identified. Considerable attention is paid to the assessment of the functioning of state administration mechanisms at the central, regional and local levels, taking into account interdepartmental coordination, digitalization, the activities of territorial communities, the role of civil society and resource provision in martial law. Based on the generalization of existing problems and imbalances, directions for improving state policy are proposed, which include the codification of veteran legislation, the formation of a single management vertical, the implementation of case management, the development of digital infrastructure, the strengthening of the mental health sector, the development of professional reintegration and project-targeted budgeting. The results obtained allow us to consider state policy in the field of social adaptation of veterans as a strategic factor of national security, social stability and post-war reconstruction of Ukraine.